Multinationals as stabilizers? Economic crisis and plant employment growth - Roberto Álvarez Espinoza; Holger Görg (Institute for the Study of Labor (IZA), 2007)
This paper examines the link between multinational enterprises and employment growth at the plant-level. We investigate in detail the comparative response of multinationals and domestic firms to an economic crisis, using the empirical setting of a well defined case of economic slowdown in Chile as a natural experiment. In our empirical analysis we find that employment growth in manufacturing plants has been drastically reduced during the economic crisis. More importantly, we do not find evidence that multinationals react to the economic crisis differently than do domestic firms. Our findings hold in a number of robustness tests, in which we also investigate the role of access to finance. The results are in contrast to the idea that multinationals are less affected by an economic crisis and that they may be able to act as stabilizers in developing countries.
Keywords: 330; Wirtschaftskrise; Beschäftigungseffekt; Anlagenbau; Multinationales Unternehmen; Verarbeitendes Gewerbe; Schätzung; Chile